2020
DOI: 10.21203/rs.3.rs-18963/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

WISP2 promotes cell proliferation via targeting ERK and YAP in ovarian cancer cells

Abstract: Background Wnt inducible signaling protein 2 (WISP2) is a wnt1-induced signaling pathway protein 2. Although studies indicate that WISP2 may promote the development of various tumors, its role in ovarian cancer remains unclear. The objective of the current study was to analyze the effects of WISP2 on proliferation and migration of ovarian cancer cells in vitro and in vivo . Results Immunohistochemistry and western blot results indicated that WISP2 was highly expressed in various ovarian tissues and cell lines.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…As one of the best characterized secreted matricellular proteins of CCN family, CCN5/Wisp2 has prominent antifibrotic actions in various tissues, such as the heart and lungs (15)(16)(17). It is significantly elevated in several ovarian cancer cell lines and tissues (18). Serum Wisp2 levels do not change in PCOS women compared to reference individuals, while Wisp2 is associated directly with fatty acid binding protein 4 (34).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As one of the best characterized secreted matricellular proteins of CCN family, CCN5/Wisp2 has prominent antifibrotic actions in various tissues, such as the heart and lungs (15)(16)(17). It is significantly elevated in several ovarian cancer cell lines and tissues (18). Serum Wisp2 levels do not change in PCOS women compared to reference individuals, while Wisp2 is associated directly with fatty acid binding protein 4 (34).…”
Section: Discussionmentioning
confidence: 92%
“…The overexpression of CCN5/Wisp2 inhibits profibrotic phenotypes in a lung fibrosis model in vivo and in lung fibroblasts separated from idiopathic pulmonary fibrosis patients (17). High expression of CCN5/Wisp2 is observed in several ovarian cancer cell lines and tissues, while deletion of CCN5/Wisp2 promotes cell apoptosis while restraining cell growth and clone formation of ovarian cancer cells (18). It is important to understand how CCN5/Wisp2 regulates fibrosis, which can be beneficial for developing novel therapeutic approaches to treat metabolic diseases, including PCOS (19).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies have reported that LIMS2 and LMOD1 can promote the migration of GC cells [40,41] . As for WISP2, researchers have demonstrated that it has a bidirectional regulatory effect on tumor cells, with WISP2 overexpression inhibiting the growth of esophageal cancer cells and its absence inhibiting the proliferation of tumor cells in ovarian cancer [42,43] . In particular, LIMS2, LMOD1, TCEAL2, TMEM100 and ZBTB16 have been reported to play important roles in the development of GC [40,41,[44][45][46] .…”
Section: Discussionmentioning
confidence: 99%
“…WISP2 (WNT1 inducible signaling pathway protein 2), which is also known as CCN5 , was overexpressed in orbitofacial NF compared to the non‐orbitofacial NF (logFC = 6 compared to non‐orbitofacial plexiform NF and logFC = 5 compared to localized intraneural NF) and a non‐neoplastic Schwann cell line (logFC = 8). WISP2 has been found to promote proliferation in ovarian cancer cells probably through ERK signaling (25). At the protein level we detected high WISP2 immunopositivity in approximately half of orbitofacial and non‐orbitofacial NFs, although MAPK signaling (pERK immunoreactivity) was higher in the orbitofacial group.…”
Section: Discussionmentioning
confidence: 99%
“…Next, to further evaluate the significance of these altered genes and pathways, we performed immunohistochemistry, evaluating protein levels (WISP2, MYC) and MAPK pathway activation (pERK) (Figure 4). Of note, a prior study highlighted a role for WISP2 expression and MAPK (pERK) activation in ovarian cancer cells (25). Furthermore, ERK is an important mediator of proliferation resulting from neurofibromin loss (26).…”
Section: Gene Pathways Enriched In Orbitofacial Nfsmentioning
confidence: 99%